Gujin Dabu tong xiang hui liu shi zhou nian ji nian te kan, 1980 (Gujin Dabu tong xiang hui, 1980)
Sixtieth anniversary souvenir of the Ku-chin ta pu tʼung hsiang hui (Kuching, Sarawak), Chinese association; comprises messages and articles on its history and activities.